Exploring Failures and Possible Remedies in AI and Human Translation of English Idioms - Li, Tianyao (Transactions on Social Science, Education and Humanities Research, 2024)
This paper explores the characteristics, similarities and differences between Chinese EFL students and AI when translating English idioms into Chinese. Based on the data collected from the questionnaire on English idioms in English-Chinese translation by Chinese EFL students and AIs, the distribution of human and AI translation accuracies and the focus of translation were analysed using the stereotyped heterogeneous ratio. The results of the survey showed these points: the overall accuracy of translations of Chinese EFL students is lower than that of AI, and the distribution of human translation accuracy among all categories of English idiom was similar to AI translation accuracy; Chinese EFL students tend to retain the form of the proverbs, while AI translators tend to translate the exact meaning; and AI is not able to fully utilise the context to facilitate the understanding of proverbs in the same way as human beings do. Based on the results, this paper expects to provide a reference for future research in this domain.